Aspects of Surgical Treatment of Spinal Pathology in the Patient with Gurler Syndrome - Polina V. Ochirova; Sergey O. Ryabykh; Tatyana V. Ryabykh (Union of pediatricians of Russia, 2021)
The clinical case of surgical treatment of combined spinal pathology in the child with Gurler syndrome is described in the article. Indications, major risk factors and aspects of surgical treatment of spinal pathology at this nosology are described in detail; all the approaches are analyzed according to the literature. Background. We would like to draw the attention of our colleagues to this problem with this clinical case. We want to emphasize the peculiarities of orthopedic manifestations in patients with mucopolysaccharidosis type IH (MPS IH). The most crucial is timely detection and surgical treatment. Clinical case description. This article describes the aspects of surgical treatment of spinal pathology in the patient with MPS IH: progressive kyphotic deformation, stenosis and craniovertebral junction instability, significant neurological deficit, internal organs functional disorders. Conclusion. Patients with MPS are characterized by multilevel orthopedic pathology which requires continuous follow-up throughout the life by single multidisciplinary team of specialists.